Case report of Osteopoikilosis in patient with psoriatic arthritis. Issue 1 (12th January 2022) - Cherif, Ines; Maatallah, Kaouther; Ferjani, Hanene; Triki, Wafa; Ben Nessib, Dorra; Kaffel, Dhia; Hamdi, Wafa
Abstract: Osteopoikilosis (OPK) is one of the rare genetic musculoskeletal, non‐inflammatory disorders that we should increase awareness toward. We report a case of a patient diagnosed with psoriatic arthritis with incidental imaging findings of lesions suggestive of osteopoikilosis. Abstract : Osteopoikilosis(OPK) is a benign, genetic, non‐inflammatory, bone disorder. The importance of acknowledging this disease resides essentially in ruling out other affections, especially malignant ones. OPK has been reported to be associated with various dermatological, cardiac, and endocrine affections. No specific therapy is required other than the treatment of the coexisting pathologies.